Enhancing High School Students’ Problem-Solving Skills in Rotational Dynamics through SPARK Model - Nurdini Nurdini; Nur Habib Muhammad Iqbal; Nuzulira Janeusse Fratiwi; Asep Irvan Irvani; Reza Ruhbani Amarulloh (Universitas Hamzanwadi, 2025)
The purpose of this study was to enhance high school students’ problem-solving skills in rotational dynamics through the STEM-Project Approach for Real-World Knowledge (SPARK) model. The study employed a quasi-experimental design with a one-group pre-test and post-test approach to measure the progress of 30 first-year students (15 males and 15 females) from a high school in Bandung, Indonesia. Validated twenty-four essay questions was used to assess students' problem-solving abilities before and after the intervention. The results demonstrated moderate improvements in problem-solving skills, with significant advancements in problem identification (N-Gain: 0.59) and the application of scientific concepts (N-Gain: 0.53), while less improvement was observed in suggesting alternative solutions (N-Gain: 0.23) and designing tools (N-Gain: 0.16). The study, analyzed through portfolios and normalized gain values, indicated medium-category increases in some aspects of problem-solving skills. It can be concluded that the SPARK model is effective in enhancing high school students' problem-solving skills in rotational dynamics, particularly in improving the identification of problems and their relation to physics concepts. However, the model was less effective in improving the design aspect, indicating the need for further development in this area. Future research should focus on creating worksheets that better align with these problem-solving indicators.